Method of Analysis of Mutasyabih Lafdzi in the Qur'an: A Study of Tafsir as-Sha'rawi - Murni, Dewi; Mahfudz, Ali; Zakiyah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
This article aims to identify and explore the analytical methods of asy-Sya’rawi in understanding the textual variations of mutasyabih lafdzi verses and their implications for Qur’anic exegesis studies. This study employs a qualitative method using thematic interpretation (maudhu’i) and content analysis approaches. The thematic approach is applied to holistically examine the phenomenon of mutasyabih lafdzi through collecting and categorizing relevant Qur'anic verses. At the same time, content analysis is used to delve deeper into Asy-Sya’rawi's interpretive methods in explaining these textual variations. The findings reveal that Asy-Sya’rawi adopts a comprehensive approach, encompassing linguistic, historical, comparative analysis, and moral and ethical insights. For instance, his study of surat al-Baqarah/2:126 and surat Ibrahim/14:35 demonstrates how the textual differences between the terms baladan and al-balad reflect the transition of a region from a barren state to a secure and thriving city. Furthermore, asy-Sya’rawi connects these verses to moral lessons emphasizing the importance of physical, social, and spiritual security in the sacred region of Haram. This article also serves as a rebuttal to the claims of Orientalists like Richard Bell and William Muir, who perceive textual variations as indications of inconsistency in the Qur’an.